Legal Resource for School Health Services - Resha, Cheryl A.; Taliaferro, Vicki (SchoolNurse.com, 2017)
A reference regarding legal issues impacting school health. The book provides information on over 50 topics that school health services programs and school nurses encounter, addresses legal implications and presents legal resources and references that can be applied to practice and policy development. - Cover
Keywords: Law and legislation; School nursing; United States; dept.nur; faculty_collection

School Nurse Resource Manual: A Guide to Practice - Taliaferro, Vicki; Resha, Cheryl A. (School Health Alert, 2017)
School nurses' work focuses directly on three areas: health services, health education, and the school environment. Their services require diverse knowledge including, but not limited to, pediatric/adolescent health, infectious diseases, mental health, chronic diseases, and emergency care. They can influence health and safety aspects of schools and can provide leadership to a district's or campus' coordinated school health program that in addition to health services, health education, and the school environment addresses mental health and social services, nutrition services, physical activity, family and community involvement, and/or staff health promotion. This work is written for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidence-based policies and procedures for safe student care.
Keywords: Handbooks, manuals, etc; School Nursing; School nursing; dept.nur; faculty_collection

Performing pediatric eye exams in primary care - Martin, E.F. (Nurse Practitioner, 2017)
Early vision care is critical for all children. If undetected, eye disorders such as amblyopia and strabismus may result in permanent vision loss. Vision exams should include a careful history and physical including fix and follow, red reflex, and cover/uncover testing. Photo screening and visual acuity exams should be administered whenever possible. © 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Adolescent; Child; Child, Preschool; Eye Diseases; Humans; Infant; Infant, Newborn; Physical Examination; Primary Health Care; Vision Screening; adolescent; amblyopia; child; children; dept.nur; eye disease; eye exam; human; infant; newborn; nursing; pediatric patients; peer-reviewed; physical examination; preschool child; primary health care; strabismus; vision exam; vision test; well-child exam

Make America wait again - Petrovic, K. (Journal of International Women's Studies, 2017)
As a means of redirecting my own personal grief that stemmed from Hillary Rodham Clinton's loss to Donald J. Trump in the most recent presidential election, I penned the following prose during the early morning hours of November 9, 2016 as Trump gave his victory speech. Like many Americans who voted in the 2016 Presidential Election, I support the right to vote for one's choice of presidential candidate; however, I am not alone in my concerns about the current presidential administration. Not only are Trump's attempts to silence the media and the right to freedom of speech cause for alarm, but his ideas on healthcare, human rights and international political relationships arguably contribute to apprehension and unease for any number of people. No presidency is without its issues, but the verse penned here may speak to others as the Trump presidency continues to unfold. © 2017 Journal of International Women's Studies.
Keywords: Donald trump; Hillary rodham clinton; United States of America; Woman president; dept.nur; ⛔ No DOI found

The benefits of taekwondo training for undergraduate students: A phenomenological study - Petrovic, K. (Societies, 2017)
The purpose of this phenomenological research was to discover whether training in the Korean martial art of Taekwondo may benefit undergraduate (UG) students in handling stress. The goal of this innovative approach to learning and stress management was to allow UG students from across disciplines at a metropolitan university achieve an increased sense of emotional balance, inner peace, and overall well-being in body, mind, and spirit. No such study has been conducted before now. This research was multidisciplinary in its inclusion of insights from the tenets of higher education, human development and psychology, nursing and sociology, as well as the art, philosophy, and sport of Taekwondo. Ten UG student participants were sought for this research study, though a total of eight students agreed to participate. The study was open to all of the UG students at this university. Phenomenology was used to identify themes that emerged regarding student participant’s experience with stress. Consequently, new ideas were established about the ways in which UG students learned to use Taekwondo training to overcome stress, thereby improving upon and maintaining health and well-being in body, mind, and spirit. © 2017 by the author; licensee MDPI, Basel, Switzerland.
Keywords: Higher education; Holistic health; Human development; Stress; Taekwondo; Undergraduate students; dept.nur

The elderly and the opioid epidemic: A case study - Green, Cheryl A. (Addictive Disorders & Their Treatment, 2017)
Opioid addiction is a problem within the United States that is impacting all age groups. The elderly are a population that is seldom discussed as being affected by opioids. Physiologically, the older adult is more susceptible for complications associated with an alteration in pharmacokinetics and late diagnosis of diseases such as viral hepatitis C. Health promotion for this population is imperative in the prevention and treatment of opioid addiction problems.
Keywords: Article; Hepatitis C virus; United States; aged; boceprevir; buprenorphine plus naloxone; case report; clinical article; creatinine; creatinine blood level; dept.nur; diamorphine; follow up; health care personnel; health promotion; hepatitis C; human; male; medicare; methadone; methadone treatment; older adults; opiate addiction; opioids; oxycodone; priority journal; protein blood level; self report; telaprevir; urea nitrogen blood level; weight reduction

Examining school-aged youth - Adimando, Andrea (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

The process for delegation in the school setting - Resha, Cheryl Ann (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education--accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education, Nursing, Baccalaureate; Educational Status; Educational Technology -- Utilization; Faculty Development; Faculty Practice; Faculty, Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools, Nursing; Self-Efficacy; Socioeconomic Factors; Students, Nursing, Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Nursing students' access to test banks: are your tests secure? - Madara, Bernadette; Resha, Cheryl; Krol, Maria D.; Lacey, Kimberly; Martin, Elaine F.; O'Sullivan, Cynthia; Smith, Jan Weingrad (Journal of Nursing Education, 2017)
Background: Schools of nursing have moved to multiple choice test questions to help prepare students for licensure and practice. However, students can buy test banks to help them “get through” nursing school. Accurate assessment of nursing students' knowledge and judgment comprises access to test banks. Method: The purpose of this exploratory study was to gain an understanding about nursing faculty's knowledge concerning test bank security issues, to assess whether publishers were aware of this issue, and vendor's reasons for supplying test banks to students. Results: Overall, the results indicated that the majority of faculty were unaware of student access to test banks, and although most do not use test banks verbatim, general consensus existed that test bank security is a concern. Conclusion: Implications include increasing faculty awareness of test bank access by students, supporting educators to develop their own test bank items, and promoting security of all examinations.
Keywords: Attitude of Health Personnel; Commerce; Databases as Topic; Education, Nursing; Educational Measurement; Faculty, Nursing; Humans; Internet; Surveys and Questionnaires; awareness; commercial phenomena; consensus; data base; dept.nur; education; exploratory research; health personnel attitude; human; human experiment; nursing; nursing education; questionnaire; student; university

Epidemiology in community health care - Jung, Betty C. (Community & Public Health Nursing: Promoting the Public's Health, 2017)
Help your students understand that community/public health nursing skills benefit their nursing practice as well as patient outcomes in acute care This student-friendly, highly visual text expands students’ viewpoints from the client-nurse relationship to a population focus. Acknowledging that population-focused tools and interventions are needed in acute care, as infection rates continue to rise and nurse-sensitive outcome indictors are closely monitored, Cherie Rector weaves in meaningful, real-life examples, case studies, and perspectives to help students understand that transitions in care are critical in today’s healthcare system. Covering a multitude of community and public settings, situations, and populations, the book helps students learn about promoting health, preventing disease (not just treating it), and protecting at-risk populations—including the elderly, the LGBT community, and veterans. This fully updated 9th Edition encourages students to think more globally and covers new innovations and emerging threats to the public’s health.KEY FEATURESNEW! QSEN sections tie key chapter concepts to quality and safety competencies, such as patient-centered care, teamwork & collaboration, evidence-based practice, quality improvement, and informatics, to help students understand the importance of these concepts.NEW! Application to Population Health explores chapter concepts from a population-focused viewpoint and offers current examples of effective population interventions.What Do YOU Think? encourages students to reflect on thought-provoking current topics or dilemmas, enhancing critical thinking skills.Evidence-based Practice demonstrates how current research examples can be applied to public/community health nursing practice to achieve optimal outcomes.From the Case Files presents case study scenarios with application-based questions, challenging students to reflect on assessment and intervention.Perspectives from nursing students, novice to expert public health nurses, faculty members, policy makers, and clients cover commonly held misconceptions about community health nursing and link between skills across settings.Healthy People 2020 highlights pertinent goals and objectives to promote health.Activities to Promote Critical Thinking at the end of each chapter challenge students, promote critical-thinking skills, and encourage active involvement in solving community health problems.Unique Levels of Prevention Pyramid boxes address a chapter topic and describe nursing actions at each of the three levels of prevention to help students understand this basic community health nursing concept. Content from the text is embedded into two integrated digital learning solutions— Lippincott CoursePoint for pre-licensure programs and Lippincott RN to BSN Online for post-licensure programs—that feature experiential, case-based instructional design aligned with the approach of the Ninth Edition. To learn more about Lippincott CoursePoint and Lippincott RN to BSN Online and to see our Video Cases, please visit http://nursingeducationsuccess.com.
Keywords: dept.nur

A new state of being: the lived experience of parental bereavement - Denhup, Christine Yvonne (OMEGA - Journal of Death and Dying, 2017)
In spite of growing bereavement literature, the meaning of the lived experience of parental bereavement is not well understood. This article presents selected findings from a Heideggerian hermeneutic phenomenological study which aimed to describe the lived experience of bereaved parents who experienced the death of a child due to cancer. Conversational interviews were conducted with six parents who experienced the death of a young child due to cancer at least one year prior to participation. The nature of parental bereavement was revealed to be a new state of being into which parents enter immediately after the death of a child and which has no end point. Findings will equip health professionals and others who work with bereaved parents with a deeper understanding of the meaning of parental bereavement.
Keywords: Adult; Bereavement; Child; Child, Preschool; Death; Female; Humans; Male; Models, Psychological; Neoplasms; Parents; Pediatric Nursing; adult; bereavement; child; child death; death; dept.nur; female; hermeneutic phenomenology; human; male; neoplasm; parent; parental bereavement; pediatric nursing; preschool child; psychological model; psychology

Town & gown: Building successful university-community partnerships - King, Beth M.; Gordon, Shirley C.; Barry, Charlotte D.; Goodman, Rhonda; Jannone, Laura T.; Foley, Marie; Resha, Cheryl; Hendershot, Candace (NASN School Nurse, 2017)
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Fifth disease (erythema infectiosum) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Homelessness - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Life Threatening cardiac conditions, (Long QT intervals and hypertrophic cardiomyopathy) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Mental health - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Service animals - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Suicide - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Teen pregnancy - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education, Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce

School nurse guidelines for: Abdomen-blunt injury - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abdominal pain / appendicitis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bed bugs - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorder - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Child abuse - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Cytomegalovirus (CMV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur